Burden of Proof Reverse as A Solution to Eradicate Bribery in Criminal Acts of Corruption - Dian Adriawan Daeng Tawang; Rini Purwaningsih (Ridwan Institute, 2022)
The assumption that corruption is seen as an extraordinary crime (extraordinaru crime) and transnational and cross-border crimes causes that in terms of eradicating it needs to be carried out in an extraordinary manner (extra ordinary counter measure). There is a stereotype in the community regarding gratification and bribery, it is difficult to prove it, so it is necessary to apply an exception (enforcement exceptionality) through the application of reversing the burden of proof which will make it difficult for the public prosecutor to escape from the snares of the law. The research’s purpose of implementing the method of reversing the burden of proof in addition to making it easier for public prosecutors to ensnare perpetrators of gratification and bribery is to minimize the occurrence of criminal acts of corruption. It is hoped that the results of this research will be able to contribute ideas and suggestions for the development of legal science, especially those related to criminal procedural law. It is also hoped that this research will become part of the library information media that provides benefits to sharpen the quality in making further research on formal criminal law. This normative research is supported by primary data, in addition to using secondary data which is a literature study in the form of laws and regulations. There is a stipulation of the method of reversing the burden of proof, shifting the burden of proof from the public prosecutor to the defendant.